AAA stewardship: managing high‐risk medications with dedicated antimicrobial, anticoagulation and analgesic stewardship programs. (16th July 2021) - Bui, Thuy; Bortz, Hadley; Cairns, Kelly A.; Graudins, Linda V.; Corallo, Carmela E.; Konstantatos, Alex; Tran, Huyen; Cheng, Allen; Dooley, Michael J.
Abstract: The first and most widely publicised pharmaceutical stewardship program has been for antimicrobials. Lack of care with antimicrobial management is a recognised risk to both patient and community safety. The core components of antimicrobial stewardship (AMS) can also be applied to other high‐risk medications, such as anticoagulants and analgesics. The authors discuss the implementation of anticoagulation and analgesic stewardship programs, based on the local AMS program principles, together forming the Antimicrobial, Anticoagulation, Analgesic (AAA) program. Amalgamated stewardship programs that focus on improving patient safety and optimising clinical outcomes beyond antimicrobials should be encouraged and adopted.